Evaluasi Penerapan Next Generation Terminal Management System (NGEN) Dalam Mendukung Kelancaran Penanganan Petikemas Pada PT. JICT di Pelabuhan Tg. Priok - Yuliani, Apri (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
The increasing throughput significantly in the Port of Tg. Priok should be well-balanced by terminal's efforts to improve facility, management, systems and information technology. Otherwise, it will bring a negative impact to the container handling performance which will influence the users' satisfaction value. Therefore, since 1 September 2009, PT. JICT has applied the Next Generation Tenninal Management System (nGen) in container handling process. The purpose of this study is to evaluate the effectiveness of the implementation of nGen in supporting the container handling process. The method used is a paired t test, to evaluate the container handling performance between pre-implementation and post implementation of nGen in PT. JICT. The advantages of nGen could bring a positive impact to the effectiveness of container handling. It doesn't only come to JICT's operator but also the users, such as Shipping Line, Freight Fonuarding, and EMKL. Tiw availability of real time data effectively improves the effectiveness of receiving and delivery process. Based on data analysis, there's a significant correlation (55,9%) for crane's average performances between pre-implementation and post implementation of nGen. 44J % is influenced by other factors such as : operator's competency, equipment's condition, ship's and yard's condition. The implementation of nGen could improve the crane's perfonnance around 0)41 to 2,059 moves. Meanwhile, there's no correlation for YOR average between pre-implementation and post implementation of nGen.Keywords : nGen, perfonnance, container terminal